2013
DOI: 10.1371/journal.pone.0068293
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell-Like Side Population Cells in Clear Cell Renal Cell Carcinoma Cell Line 769P

Abstract: Although cancers are widely considered to be maintained by stem cells, the existence of stem cells in renal cell carcinoma (RCC) has seldom been reported, in part due to the lack of unique surface markers. We here identified cancer stem cell-like cells with side population (SP) phenotype in five human RCC cell lines. Flow cytometry analysis revealed that 769P, a human clear cell RCC cell line, contained the largest amount of SP cells as compared with other four cell lines. These 769P SP cells possessed charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…The combination of Cis-P and ATO also depleted CSC, thereby offering yet other mechanisms for targeting RCC. The SP population in RCC may often be in G0/G1 although this may need more characterization (18,19). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of Cis-P and ATO also depleted CSC, thereby offering yet other mechanisms for targeting RCC. The SP population in RCC may often be in G0/G1 although this may need more characterization (18,19). …”
Section: Discussionmentioning
confidence: 99%
“…Our studies included HuH-7 cells, which originated from an adult HCC (17), and displayed robust Cis-P-induced DDR (4). In these ways, we obtained information in respect to DDR in HK-2 cells, including cell growth regulation in the context of p53-related intracellular signaling, and the “side population (SP)” often associated with cancer stem cells (CSC) (18,19). This helped us to determine whether drugs could be identified with capacity for synergistically amplifying Cis-P toxicity in renal cells.…”
Section: Introductionmentioning
confidence: 99%
“…However cancer stem -like cells in five human RCC cell lines were identified [70]. These cells displayed high potential for proliferation and self-renewal, as well as strong resistance related to the ABCB1 transporter.…”
Section: Novel Dimensions In Comprehensive Approach the Mechanisms Ofmentioning
confidence: 99%
“…Previous studies have demonstrated that SPs within different cancer cells are less differentiated and have characteristics of stem/progenitor cells (7,16,21). In addition, it has been confirmed that SP cells in RCCs exhibit TIC characteristics (8,9,22). Fig.…”
Section: Fractionated Irradiated Cells Exhibit High Tumorigenicity Anmentioning
confidence: 63%
“…A number of studies have isolated pools of TICs from RCC cell lines and tumor specimens (9)(10)(11)(12)(13)(14). RCC TICs appear to be responsible for malignancy progression, relapse and metastasis (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%